Numerical study of low-speed impact response of sandwich panel with tube filled honeycomb core - Liu, J.; Chen, Wensu; Hao, Hong; Wang, Z. (ELSEVIER SCI LTD, 2019)
© 2019 Elsevier Ltd Sandwich panel with Honeycomb Filled with Circular Tubes (HFCT) as core is numerically investigated by using ABAQUS/Explicit in this study. To calibrate the numerical model, the panels equipped with conventional hexagon honeycomb cores are modeled. Good agreement between numerical and experimental results is achieved. The sandwich panels with HFCT are compared with the sandwich panels with Honeycomb and Multi-tube cores of identical mass subjected to vertical and oblique impacts. The maximum displacement of face-sheets, plastic energy absorption, boundary reaction forces and impact load time history are calculated to assess the impact resistant capacity. The panel with HFCT core has smaller rear face-sheet displacement and higher energy absorption capacity as compared to the panels with the Multi-tube and Honeycomb core. Under oblique impact, both HFCT and Multi-tube panels have superior impact resistant capacity than the Honeycomb panel. In addition, the impact resistances of four types of multi-arc tube filled Honeycomb (HFMT) are also analysed. Their performances under vertical and oblique impacts are compared with those of HFCT.